A comparative study of serum uric acid, glucose, calcium and magnesium in pre-eclampsia and normal pregnancy (Journal of Pathology of Nepal, 2017)
Background: Preeclampsia is associated with liver function abnormalities and renal function impairment. The objective of this study is to compare serum uric acid, glucose, calcium and magnesium in pre-eclampsia with normal pregnancy. Materials and Methods: Normal pregnant women and pre eclamptic women of age group 20-40 years were included. Serum magnesium, calcium, glucose, uric acid were analyzed.Results: Mean serum magnesium level in preeclampsia (1.83 ± 0.21mg/dl) was lesser in comparison to normal pregnant women (2.03 ± 0.16 mg/dl). Serum calcium level was lower (8.10 ±0.56mg/dl) than control (9.59 ±0.62 mg/dl) with p